Pendampingan Study Tour Napak Tilas Bung Karno Kepada Siswa-Siswi Sdi Kotakeo Sebagai Salah Satu Wisata Edukasi Wawasan Kebangsaan Nasional, Kabupaten Ende, Nusa Tenggara Timur - Emiliana Laku Mali; Novia Dewi Anisa (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
This activity also serves as a good form of Educational Tourism for students. Referring to one of the functions of history education that can be taught in schools is history as moral education. Every historical event has values ​​and morals that can be taken as lessons for today's life. In addition to its educational function, history also has learning objectives. The Community Service Team will conduct a historical journey of Bung Karno's Remembrance in Ende Regency, East Nusa Tenggara Province. The number of participants in the activity is 50, consisting of accompanying teachers and students. SDI Kotakeo is an elementary school located in Mabharobo, Kotakeo I Village/Sub-district, Nagaroro District, Nagakeo Regency. The purpose of this activity is to restore a sense of nationalism in their lives and themselves (Maola Sofiatul Putri, 2021). In addition, students can learn about the historical track record of the inception of Pancasila by the First President Ir. Soekarno in Ende City. The study tour, which will be held in Ende, focuses on educational activities. Participants are guided to understand the value of Sukarno's struggle through visits to historical sites, including the House of Exile and the Veranda.